Kolaborasi Antara Aparatur Birokrasi Pemerintah Daerah Istimewa Yogyakarta dan Forum Pengurangan Risiko Bencana (FPRB) DIY Dalam Penyelenggaraan Penanggulangan Bencana di Daerah Istimewa Yogyakarta - Dwi Agustina (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
Yogyakarta Special Region (DIY) can be regarded as a mini-disaster laboratory, this is because the potential for disaster in DIY is very big. DIY has 12 disaster threats: Flood, Epidemic & Outbreak, Extreme & Abrasion, Extreme & Abrasion, Earthquake, Tsunami, Failure Technology, Drought, Volcano Eruption, High winds, Landslide, Fire and Social Disasters.With the existence of several types of threats Disaster is certainly a challenge for the Government of Yogyakarta Special Region. The government is expected to be better prepared to reduce the risk of casualties in the event of a disaster. Implementation of disaster management can not be done by one party only, in accordance with the mandate of Act No. 24 of 2007 stating that the implementation of disaster management government should not do alone and must involve multi stakeholders.This research uses descriptive qualitative research method, with data collecting technique through direct observation, in-depth interview with Pemeriintah Daerah Istimewa Yogyakarta, BPBD, and some members of PRB Yogyakarta Forum. and review of written documentation.Local Government of Yogyakarta realized that multi-stakeholder involvement is needed in disaster management. on the basis of the initiation of various stakeholders involved in the implementation of disaster management during the earthquake bantul then formed a forum as a forum for gathering of stakeholders from various elements of the Forum Disaster Risk Reduction or more often called DIY DRR Forum. With this froum the actors perform their respective functions by coordinating and working together.This study, which refers to the collaboration between the DIY Government and DIY DRR Forum, has resulted that the implementation of Disaster Management in Yogyakarta has now been done by various multi-actors collaboratively. Each actor has been divided into roles according to their respective expertise. In Collaborative Governance can be seen through two dimensions of the Context System and the driving dimension. Through these two dimensions in this study see how the collaboration between DIY Government and Froum DRR DIY.